Efisiensi Kinerja Rantai Pasok Beras Organik “Beras Raos” - Rizqia Fauziah; Endang Tri Astutiningsih; Neneng Kartika Rini (Jurnal Sosial Ekonomi Pertanian, 2021)
Nowadays people are starting to realize the importance of healthy food, such as organic rice. It's just that economically the rice agricultural sector still faces various problems, one of which is the selling price at the farm level which is still relatively low, this is because the supply chain is still long and the supply chain system is less than optimal. The purpose of this study was to analyze the performance efficiency of the organic rice supply chain "Beras Raos". The research method used is a survey method, with farmer respondents, Sari Alam farmer groups, and retailers determined using purposive sampling and snowball sampling. Data analysis uses descriptive analysis with a quantitative approach, and aspects of marketing efficiency analysis (marketing margin and farmer's share) and asset management efficiency (inventory turnover, inventory days of supply, and cash to cash cycle time). The results of the analysis of the efficiency of the supply chain performance show that it is not fully efficient, such as: the value of farmer's share which is still <70%, which only reaches 41.8% and the value of cash to cash cycle time which reaches 37 days to convert organic rice supplies into cash, where the 37 day period is still quite long.